The Reproducibility of an Abbreviated Fat Tolerance Test in Young Healthy Participants: A Pilot Study (P12-029-19). (13th June 2019) - Dixon, Madison; Sciarrillo, Christina; Koemel, Nicholas; Emerson, Sam
Abstract: Objectives: Triglyceride (TG) responses following a high-fat meal are more strongly associated with cardiovascular disease (CVD) risk compared with fasting TG levels. The current protocol for assessing post-meal TG is a burdensome process, involving serial blood draws for up to 8 hours. We have developed an abbreviated fat tolerance test (AFTT) that yields highly similar TG results relative to the standard protocol. The objective of this study is to determine whether the AFTT is reproducible and how it compares to the reproducibility of the oral glucose tolerance test (OGTT), a metabolic challenge already in clinical use. Methods: In a randomized crossover design, 6 healthy participants (2 M/4F, age: 25.8 ± 9.4 years, BMI: 22.6 ± 2.6 kg/m², fasting TG: 69.8 ± 9.8 mg/dL, fasting glucose: 93.5 ± 5.1 mg/dL, A1C: 5.3% ± 0.34%) completed 2 AFTT's separated by 1 week followed by 2 OGTT's separated by 1 week, or vice versa. There was a 2-week washout period between the AFTT's and OGTT's. For each AFTT and OGTT, a baseline blood draw was taken followed by either consumption of a high-fat shake (73% fat, 26% CHO; 9 kcal/kg) (AFTT) or a standard 75 g glucose drink (OGTT). Following consumption of the AFTT, participants left the lab and returned 4 hours later for a post-meal blood draw. Following consumption of the OGTT, participants remained in the lab for 2 hours and a post-meal blood draw was taken. Results: The mean difference in 4-hour postprandial TG change from baseline between the 2 AFTTs was 5.2 mg/dL, while the mean difference in 2-hour glucose change between the 2 OGTTs was 17.5 mg/dL. The 4-hour TG change results from the 2 AFTT's were highly correlated ( r  = 0.96, P  = 0.003), while the 2-hour change results from the 2 OGTTs were not ( r  = 0.17, P  = 0.75). The within-subjects coefficient of variation (WCV) for 4-hour TG concentrations between the 2 AFTT's was 16%, suggesting moderate reproducibility, while the WCV for 2-hour glucose concentrations between the 2 OGTT's was 24%, indicating low reproducibility. Conclusions: These preliminary data suggest that the AFTT response is reproducible, potentially more than the OGTT. While further assessment in a larger sample is necessary, the AFTT could advance postprandial TG testing toward greater clinical feasibility. Funding Sources: Funding provided by internal sources at Oklahoma State University.